ANALISIS SEKTOR UNGGULAN DAN POTENSI EKONOMI DI PROVINSI BALI PASCA PANDEMI COVID-19 - Pratiwi, Ida Ayu Meisthya; Apsari Anandari, I Gusti Agung Ayu; Dyastari Saskara, Ida Ayu Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023, 2023)
To revive the economy of the Bali Province after the Covid 19 Pandemic, regional development is needed that focuses on developing leading sectors and potential sectors. This research was conducted in 17 economic sectors in 9 regencies/cities in Bali Province during 2017-2022 using a quantitative descriptive analysis method with the Location Quotient (LQ) analysis technique and Klassen Typology. The results of the average calculation using LQ analysis show that there are 6 leading sectors in Bali Province, namely agriculture, forestry and fisheries; mining and quarrying sector; processing industry sector; Health service sector and social activities; Government Administration, Defense and Compulsory Social Security sectors; and other service sectors. Based on the Tipoloi Klassen analysis, the results obtained were that the sectors included in the same leading sectors in all regencies/cities of Bali Province were agriculture, forestry and fisheries; Government Administration, Defense and Compulsory Social Security and other service sectors. The potential sector is the Mining and Quarrying sector; Procurement of Electricity and Gas; Transportation and Warehousing; Provision of Accommodation and Food and Drink; and Education services. Meanwhile, the developing sector is the real estate sector, and the underdeveloped sector is the corporate services sector and the health and social activities sector.